Motor Penggerak Merdeka Belajar Bagi Aparatur Sipil Negara (ASN) - Lesmana, Widi; Kurohman, Novik (Lembaran Ilmu Kependidikan, 2022)
The Civil Servant (ASN) is obliged to carry out self-competence development. Widyaiswara as a facilitator during the training has to support the flexibility in self-development of ASN. A widyaiswara is required to be able to build relationships with trainees, class management, use information technology, and implement learning innovations that are relevant to the character of the trainees. The purpose of this study is to describe the competency profile that must be possessed by widyaiswara as a driving force for independent learning for ASN. The method used in writing this article is Systematic Literature Review (SLR). This method is a systematic way to collect, critically evaluate, integrate and present findings from various research studies on research questions. The results of the discussion show that a widyaiswara must have digital skills in planning learning, using learning media, learning methods, evaluating learning, the concept of independent learning, and acting as a driving force for ASN and training participants. The use of digital media can develop the self-competence of a Widyaiswara